{Fate of the C-1′ peroxyl radical in the 2′-deoxyuridine system} - Chatgilialoglu, Chryssostomos; Gimisis, Thanasis (Chem. Commun., 1998)
The mechanism of 2-deoxyribonolactone formation from the reaction of photogenerated 2′-deoxyuridin-1′-yl radical with molecular oxygen in water has been investigated.